(untitled) (Global Journal of Human-Social Science, 2021)
One of the common challenges facing practitioners is the critical speaking fluency of EFL learners. Many students find immense challenges in communicating their ideas, let alone finding the appropriate and practical modalities to communicate authentically outside the classroom walls and measuring it. This paper aims at exploring the impact of educational technology on students’ oral fluency. To gauge the intended impact, a quantitative method is used. Educational technology is used as an independent variable with an insightful historical overview of the term, whereas oral fluency, the dependent variable, is narrowed down into measurable descriptors. The findings of this study inform the literature with the importance of the implementation of educational (instructional) technology into refining the teaching practices via an empirical evidence on the one hand and improving the speaking (oral) skills by the affordances supplied by the app and software designed for testing the validity of the data. This paper is concluded with some limitations and recommendations to open more horizons for action research and investigate the debated topic under study.